Digging for Growth? Which infrastructure development should African countries prioritise? - Modise, Mpho (Graduate School of Business (GSB), 2022)
This study investigates the impact of infrastructure development on economic growth among 10 selected African countries over a period of 15 years from 2000 – 2015. The study uses panel data to analyse the effect of infrastructure components on economic growth. The findings show that infrastructure development impacts economic growth, and further identifies that African countries should prioritise investing in Power and the Human Development Index (HDI). These results suggest a need for reform in policies and planning. African states will be required to invest time in planning their infrastructure investment in advance with clear timelines and funding requirements. To attract Foreign Direct Investment (FDI) in power infrastructure, States will need to reform both monetary and political policies to create an attractive investor environment. Lastly, States will need to reform fiscal policies to prioritise investment in the HDI.